Management Approaches and Strategies by the Farmers to Cope Up with the Risk of Covid-19 Pandemic - Ashad, Rahul; Roy, Tuhin Narayan (International Journal of Bio-resource and Stress Management, 2023)
This study was conducted under the department of Agricultural Economics, Uttar Banga Krishi Viswavidyalaya, Coochbehar, West Bengal, India during October, 2021 to January, 2022. The objective was aimed to evaluate the management approaches in relation to management principles for sustaining their farming during Covid-19 pandemic with a unique set of primary data (before, during and after of pandemic) collected in Jalpaiguri district, West Bengal, India. Tabular, multiple regression and Garrett ranking analysis were followed to obtain the results for interpretation. Impact of the management approaches was reflected in positive net income (return-cost ratio around 1.09) in spite of variation in yield and price for two crops viz. paddy and wheat. Mobile phone was largely used for transaction. Multiple regression analysis predicted some independent variables responsible for low yield. The study, thus, showed the farmers’ managerial strategies during pandemic helped them to maintain livelihoods. Restriction in consumption, saving, entertainment, investment and other expenditures had been evident. Low risk enterprises like livestock and vegetables were followed to reduce risk. Like a visionary manager, majority of the farmers (76%) prioritised (Garrett ranking) on more Govt. initiatives. Extent and variation of management principles (functions) viz. planning, organizing, leading and controlling, as followed by the farmers was also examined and found to be relevant. The study, thus, showed the managerial strategies and efficiency of farmer-manager during pandemic which helped the farmers’ to sustain livelihoods during pandemic.